Optimalisasi Pelaksanaan Program Kolektif Untuk Meningkatkan Kompetensi Guru Sebagai Evaluator Dalam Menyusun Soal UAS di SDN Bakalan Kecamatan Sumobito Tahun Pelajaran 2018/2019 - Latifah, Umi (Universitas Negeri Surabaya, 2020)
The principal has an important role in leading the school to realize better education. In school-based management, the implementation of school programs is supported by democratic and professional leadership. The principal is a professional education manager. Therefore it is necessary to improve the ability of the board of teachers who become partners in the education unit they lead in terms of assessing the learning process both in the process of making, implementing and analyzing it. Basically, this assessment aims to make the Bakalan Elementary School teacher have the ability to compile the Final Examination Test questions (UAS) properly in accordance with the rules of writing correct questions. This research is based on the formulation of the problem: Whether by optimizing the implementation of the Collective program that has been compiled can improve teacher competency as an Evaluator in compiling the test questions End of Semester (UAS) in SDN Bakalan Sub-district Sumobito Jombang district in the school year of 2018/2019. The method needed in this study was obtained through observing the processing of activities compiling the End of Semester questions through Collective program activities. Based on data analysis, from this study it can be concluded that the application of the Collective program in compiling the End of Semester Test (UAS) is very effective. Through the Collective program can also improve the ability of teachers in compiling a good test this is seen in the first cycle and cycle activities second, with a very significant increase, from an average value of 66.7 with a percentage of completeness of 45.5% to an average test score of 85.7 with a percentage of completeness of 100%. Tests are considered feasible if at least 75% of the criteria can be met.Â